Utilization of Solar Panels as a Source of Electrical Energy in Alternating Current (AC) Water Pump - Masthura Masthura; Armansyah Armansyah (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Solar panels are an alternative power generation system sourced from the absorption of solar energy. The solar energy absorbed will convert into a source of electricity. The solar panel's power drives an alternating current (AC) water pump. This study aims to determine the performance of the AC water pump by utilizing electrical energy sourced from solar panels. The parameters measured are voltage, current, and power generated by the AC water pump at varying times. The solar panels used with a capacity of 100 WP were connected to a solar charge controller (SCC), which was connected to a battery, and an inverter functions as a tool to convert DC  to AC. The results were obtained from solar panels that can optimally drive the AC water pump. At 10.00 WIB, the electric voltage was 17.68 volts, the electric current was 4.98 amperes, and the electric power was 88.04 Watts. At 15.00 WIB, with clear weather conditions,  an electric voltage of 18.90 volts, an electric current of 6.22 amperes, and an electric power of 117.55 Watts were obtained.